Genetic analysis of self-reported physical activity and adiposity: The Southwest Ohio Family Study - Choh, Audrey C (2008)
OBJECTIVE: Physical inactivity poses a major risk for obesity and chronic disease, and is influenced by both genetic and environmental factors. However, the genetic association between physical activity (PA) level and obesity is not well characterized. Our aims were to: (i) estimate the extent of additive genetic influences on physical activity while adjusting for household effects; and (ii) determine whether physical activity and adiposity measures share common genetic effects. SUBJECTS: The sample included 521 (42% male) adult relatives, 18–86 years of age, from five large families in the Southwest Ohio Family Study. DESIGN: Sport, leisure and work PA were self-reported (Baecke Questionnaire of Habitual Physical Activity). Total body and trunk adiposity, including percentage body fat (%BF), were measured using dual-energy X-ray absorptiometry. Abdominal visceral and subcutaneous adipose tissue mass were measured using MRI. RESULTS: Heritabilities for adiposity and PA traits, and the genetic, household and environmental correlations among them, were estimated using maximum likelihood variance components methods. Significant genetic effects (P<0.05) were found for sport (h(2) = 0.26) and leisure PA (h(2) = 0.17). Significant (P<0.05) household effects existed for leisure PA (c(2) = 0.25). Sport PA had a negative genetic correlation with central adiposity measurements adjusted for height (ρ(G)>|−0.40|). Sport and leisure PA had negative genetic correlations with %BF (ρ(G)>|−0.46|). CONCLUSIONS: The results suggest that the association of sport and leisure PA with lower adiposity is due, in part, to a common genetic inheritance of both reduced adiposity and the predisposition to engage in more physical activity.